Contribution of Depolarization and Repolarization Changes to J-Wave Generation and Ventricular Fibrillation in Ischemia - Tsvetkova, Alena S.; Azarov, Jan E.; Bernikova, Olesya G.; Ovechkin, Alexey O.; Vaykshnorayte, Marina A.; Demidova, Marina M.; Platonov, Pyotr G. (Frontiers in Physiology, 2020)
Background. Activation delay in ischemic myocardium has been found to contribute to J-wave appearance and to predict ventricular fibrillation (VF) in experimental myocardial infarction. However, the role of ischemia-related repolarization abnormalities in J-wave generation remains unclear. Objectives. The objective of our study was to assess a contribution of myocardial repolarization changes to the generation of the J wave in the body surface ECG and VF in a porcine acute myocardial infarction model. Methods. In 22 anesthetized pigs, myocardial ischemia was induced by occlusion of the left anterior descending coronary artery (LAD, n=14) and right coronary artery (RCA, n=8). Body surface ECGs were recorded simultaneously with intramyocardial unipolar electrograms led from flexible electrodes positioned across the left ventricular (LV) wall, interventricular septum (IVS), and right ventricular (RV) wall at the apical, middle and basal levels of the ventricles (a total of 48 leads). Local activation times (ATs) and activation-repolarization intervals (ARIs, differences between dV/dt maximum during T-wave and dV/dt minimum during QRS) were measured. Results. J-waves appeared in left precordial leads (in 11 out of 14 animals with LAD occlusion) and right precordial leads (in 6 out of 8 animals with RCA occlusion). During ischemic exposure, ATs prolonged, and the activation delay was associated with J-wave development (OR=1.108 95% CI 1.072-1.144; p<0.001) and VF incidence (OR=1.039 95% CI 1.008-1.072; p=0.015). ARIs shortened in the ischemic regions (in the IVS under LAD-occlusion and the lateral RV base under RCA-occlusion). The difference between maximal ARI in normal zones and ARI in the ischemic zones (ΔARI) was associated with J wave appearance (OR=1.025 95% CI 1.016-1.033, p<0.001) independently of AT delay in multivariate logistic regression analysis. Conclusions. Both AT delay and increase of ΔARIs contributed to the development of J-wave in body surface ECG. However, only AT delay was associated with VF occurrence.